2003
DOI: 10.1016/j.susc.2003.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of Ni bulk, surfaces and the adsorbate systems Ni(111)R30°–Cl, and Ni(111)(2×2)–K

Abstract: Nickel bulk, the low index surfaces and the adsorbate systems Ni(111) ( √ 3 × √ 3)R30 • -Cl, and Ni(111)(2 × 2)-K are studied with gradient corrected density functional calculations. It is demonstrated that an approach based on Gaussian type orbitals is capable of describing these systems. The preferred adsorption sites and geometries are in good agreement with the experiments. Compared to non-magnetic substrates, there does not appear to be a huge difference concerning the structural data and charge distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
3
16
0
Order By: Relevance
“…We have calculated magnetic moments of the Ni electrodes and the obtained values for the first three layers in the unit of µ B are 0.632, 0.661, and 0.629 for (111) surface, and 0.743, 0.626, and 0.637 for (100) surface, which are in excellent agreement with those reported in the literature 39,40 with difference less than 2.5% compared to the values in Ref. 40.…”
supporting
confidence: 87%
“…We have calculated magnetic moments of the Ni electrodes and the obtained values for the first three layers in the unit of µ B are 0.632, 0.661, and 0.629 for (111) surface, and 0.743, 0.626, and 0.637 for (100) surface, which are in excellent agreement with those reported in the literature 39,40 with difference less than 2.5% compared to the values in Ref. 40.…”
supporting
confidence: 87%
“…The pseudopotential helps to reduce the computational effort, and, maybe even more important, offers the possibility to include scalar-relativistic effects. The Gaussian basis sets are: a [3s2p] basis set or a [4s3p] basis set for Li [10], [6s5p2d] basis sets for Cu [11] and Ni [6], a [4s3p2d] basis set together with a 19-valence electron pseudopotential for Ag [12], a [4s4p2d] basis set for Pt together with a 18-valence electron pseudopotential [13], and [5s4p1d] basis sets for Cl [11], and K [14]. k-point nets of the size 16 × 16 were used, and the smearing temperature was in the range between 0.001 E h and a maximum value of 0.01 E h , as described earlier [10,11,12,13,15].…”
Section: Methodsmentioning
confidence: 99%
“…In earlier calculations on nickel surfaces [6], without using ghost atoms, it had already been shown that varying the outermost diffuse exponent changed the work function strongly, but the other properties such as the geometry, relative energies of the adsorption sites or Mulliken populations were only weakly affected. As the relative energies of the various sites are very important, the relative energies with and without ghosts were computed, as a further test for the system Cl/Cu(111).…”
Section: Adsorbate Systemsmentioning
confidence: 99%
“…substrate rumpling). This was done for the top site where this effect is expected to be most important [18,19]. This led however, to only a very small change in the binding energy and is thus negligible.…”
Section: Slab Modelmentioning
confidence: 99%